Regional Programs on Energy Saving and Energy Efficiency: The National Construction Sector - Filushina, Kristina E.; Minaev, Nikolay N.; Gusakova, Nataliya V.; Dobrynina, Olga I.; Zharova, Ekaterina A.; Merkuleva, Yuliya A.; Runkova, Anastasia S. (International Journal of Economics and Financial Issues, 2016)
The research is aimed at identifying patterns of implementation of regional programs for energy saving and increasing energy efficiency in the context of innovative development of the construction industry. Authors held a critical analysis of the existing regional programs in the field of energy saving, the development of proposals for improvement of existing and development of new energy efficiency programs for the building complex, including low-rise housing construction. The study applies economic and statistical methods as to establish quantitative relationships and evaluation of existing programs for the development of new instruments of territorial-sectoral development. The conclusions are made on the overall inefficiency of the implementation of existing regional programs on energy saving and energy efficiency, as well as the need to change them in terms of the introduction of industrial components. Implementation of the results can lead to performance improvement of both the regional energy efficiency programs, and the development of the construction industry. Keywords: construction industry, regional development, energy conservation, energy efficiency. JEL Classifications: R63, R11, Q48